Development of Mechanical Casing Structure of SWAD (Signal Warning Detector) - Abdul Rashid, Muhammad Amir Raauf; Hassan, Suhaimi (Research Progress in Mechanical and Manufacturing Engineering, 2022)
There are several safety procedures while conducting maintenance and repairing on the highway. Unfortunately, there has an accident among workers and vehicles. This application of Signal Warning Detector is invention to help to reduce the incidents that involves the maintenance worker and vehicles at the highway. This system detects using sensor, whenever vehicles near the construction site within 100 meters and giving signal to alert the workers and the vehicles. Some problem has been stated according to the previous design of the casing that is not suitable for the environment and the situation at the highway that is exposed to the heat and rain. Improvement has been done by reconstruct the design and changing the material that use at the casing of the transmitter and the receiver from ABS (Acrylonitrile Butadiene Styrene) to Cast nylon 6 for transmitter and Polyoxymethylene Copolymer for the receiver. Using the Solidworks simulation to get the analysis result of the strength and rigidity of the design. From the result, the new design with new material giving better improvement from the previous design and it is suitable to use at the highway.